You are on page 1of 16

Norm-Induced Inner Products

(Solution to a Practice Exercise)

Jon Gomez <jgomez @ pcs.cnu.edu> 2009

Introduction
This is the solution of an exercise from the book Fourier and Wavelet Analysis1 . The exercise deals with the derivation of inner products from norms. It states a derivation formula, the polarisation identity, and a parallelogram law as a necessary condition for the identity to produce an inner product. The book then asks the reader to provide the proof. Here I present such a proof. The norm and inner product are functions of one and two vectors (respectively). The norm is an abstraction of the notion of length. The inner product and norm together can provide an abstraction of angles between vectors. Neither has a set definition, only a collection of properties they must satsify, and so it is not hard to come up with such functions for arbitrary, even infinite, dimensional vector spaces. Vectors themselves are also rather abstract concepts for the same reason, that is, they need only satisfy a collection of properties to be called a vector. For example, when vectors are first introduced, directed line segments are commonly used as an example, but more advanced books make frequent use of functions as vectors. Thus, a statement about the relationship of norms and inner products is very general indeed. Here is the problem exercise formally stated (formal definitions follow in another section):

1 Pages 22-23. Bachman, Narici, and Beckenstein. Fourier and Wavelet Analysis. Published by Springer-Verlag New York in 2000. ISBN 0-387-98899-8.

1

In contrast. Definitions Definition (Complex Inner Product). 0 can be either the zero vector (in S) or 0 ∈ R. x. • I is the set of imaginary numbers without a real component. This is usually proven with the Cauchy-Schwarz inequality in elementary textbooks on linear algebra. • Unless otherwise stated. • Unless otherwise stated.Given a norm x that satisfies the parallelogram law. the norm to inner product derivation stated above is restricted to norms that satisfy the parallelogram law. y .b are arbitrary complex numbers. The inner product is a complex-valued function of an ordered pair of vectors (in S) such that the following properties hold: 2 . that x = The last condition states that the norm produced by the inner product in the regular manner corresponds to the norm that was used to define the inner product.z are arbitrary vectors in S. • x is the norm of x. • x. showing that the conversion is two-way. show x. show that the polarisation identity defines an inner product x. • Depending on context. Notation • R is the set of real numbers. • S is an arbitrary vector space. x . y is the inner product of x and y. • Lemmas that do not assume the parallelogram law (stated below) are marked with a star. • C is the set of complex numbers (C = R × I).y. It is worth mentioning that the reverse operation of deriving a norm from an inner product is always possible for any inner product. a. Furthermore.

then. 3 . The parallelogram law holds only for certain norms: x+y 2 + x−y 2 =2 x 2 + 2 y 2. z + y. z = x. We shall show that this is indeed an inner product. Definition (Polarisation Identity). y according to the polarisation identity. y = y. and that x 2 = x. Then define a function x.Conjugate Symmetry Linearity x. x ≥ 0 x. it is a suitable definition for an inner product in terms of a norm. that we have a norm x that satisfies the parallelogram law. x ∈ R and x. z x. The polarisation identity holds between inner products and the norms that are derived from them. y (which is an inner product only under the stated conditions): x. x = 0 ⇐⇒ x = 0 Positive Definiteness Definition (Norm). y = 1 4 x+y 2 − x−y 2 + i x + iy 2 − i x − iy 2 Propositions Let us suppose. In the other direction. y) x + y. y = a(x. x . The norm is a real-valued function of a vector which satisfies the following properties: Positive Definiteness x ∈ R and x ≥ 0 x = 0 ⇐⇒ x = 0 x+y ≤ x + y ax = |a| x Triangle Inequality Homogeneity Definition (Parallelogram Law). as shall be shown in this paper. It may be thought of as defining a function x. if that norm satisfies the parallelogram law. x ax.

For example. y ∈ S.Sum Formula We introduce a useful summation formula for inner products here. 4 . set the x in the law to a−b and the y in the state1 ment of the law to x−y and the sum becomes 2 (a − b) + (x − y) 2 + (a − b) − (x − y) The result is a. Applying the parallelogram law. y = 1 2 a − x. b + x. Lemma 1. For all a. Using the polarisation identity. the two inner products in the left hand can be re-written in terms of norms: 1 4 1 x. for a−b 2 + x−y 2 . y = 4 a. y = 1 4 a+b − 2 + x+y 2 1 a−b 2+ x−y 2 4 1 + i a + ib 2 + x + iy 4 1 − i a − ib 2 + x − iy 4 2 2 . b. x. a. + (a + b) − (x + y) 2 11 (a − b) + (x − y) 2 + (a − b) − (x − y) 2 42 11 i (a + ib) + (x + iy) 2 + (a + ib) − (x + iy) + 42 11 − i (a − ib) + (x − iy) 2 + (a − ib) − (x − iy) 42 2 2 . b = a+b x+y 2 − a−b − x−y 2 + i a + ib + i x + iy 2 − i a − ib 2 2 2 2 − i x − iy 2 The columns of terms with corresponding coefficients may be added: a. y = 11 42 − (a + b) + (x + y) 2 2 . b + y + Proof. b + x. these grouped sums can be transformed. b + x. b − y . 1 2 a + x.

♦ Special Cases In this section we deal with some special cases of the inner product. y = 0. y = a x.Some algebra to shuffle around some of the inner parts of the norms produces a. b + x. y = 11 42 11 42 (a + x) + (b + y) i(b + y) 2 2 2 2 − (a + x) − (b + y) 2 2 + i (a + x)+ − i (a + x) − i(b − y) 2 + 2 (a − x) + (b − y) i(b − y) 2 − (a − x) − (b − y) 2 + i (a − x)+ − i (a − x) − i(b − y) . x. y for particular values of a. For the case x. Lemma 2. 0 = x + 0 = x = 0. y = This is the desired result. b + x. We show ax. b − y . These grouped expressions correspond to particular inner products: 1 1 a + x. 0 = 0. b + x. − x +i x . 0 . 2 2 a. Proof. it suffices to use the polarisation identity and algebra: x. y = 11 42 − (a + x) + (b + y) 2 + (a − x) + (b − y) 2 11 (a + x) − (b + y) 2 + (a − x) − (b − y) 2 42 11 + i (a + x) + i(b + y) 2 + (a − x) + i(b − y) 42 11 − i (a + x) − i(b − y) 2 + (a − x) − i(b − y) 42 Now the outer parts can be separated and regrouped: a. 5 2 2 − x−0 2 2 2 + i x + i0 −i x 2 2 − i x − i0 2 . b + y + a − x.

−iy = i x. y = (i)(−i)( x − iy 2 − x + iy 6 2 + i x + y − i x − y ). 2x. 4 ix. Hence. 2y . x. Utilizing lemma 1 and lemma 2. y 2 2 1 = 2x. 0. Factoring out the i inside the norms and then using the homogeneity property of the norm yields 4 ix. Since i × −i = 1. ♦ Lemma 3. 0 and 0. y + 0 + 0. y . 0 1 1 = x + x. Since |i|2 = 12 = 1. ix. y + y + −x.By a similar argument. y . Proof. y = 0. y + x. y = x. y = x − iy 2 − x + iy 2 +i x+y −i x−y . y 1 1 = 0 + x. 2y = 2 x. the equation becomes 4 ix. 2 ♦ Lemma 4. y are also equal to each other. since they are both equal to the zero vector. y = 0. y = x. 2 The rest of the proof follows similarly: x. y + x. y = ix + y 2 − ix − y 2 + i ix + iy 2 − i ix − iy 2 . By the polarisation identity. the entire right-hand side may be multiplied by the expression: 4 ix. Proof. y = x. y . y = |i|2 x + i−1 y 2 − |i|2 x − i−1 y 2 + i|i|2 x + y − i|i|2 x − y . . one part is easily shown: x. 0 2 2 1 = x.

the inner product can be expanded: −x. y = x − y 2 − x+y 7 2 + i x − iy 2 − i x + iy 2 . by the polarisation identity. −y = − x. (−1)a = (| − 1|) a = (1) a = a . Proof. ix. This yields −x. y = i ( x + y − x − y + i x + iy 2 ) − i x − iy 2 . Using the polarisation identity. y = − x + y 2 − −x−y 2 2 + i − x + iy 2 2 − i − x − iy 2 2 = (−1)(x − y) − (−1)(x + y) + i (−1)(x − iy) − i (−1)(x + iy) 2 . y . y . 4 which is. this becomes 1 ix. y = i( x + y − x − y + i x + iy 2 − i x − iy 2 ). −iy = i x. After dividing both sides by 4. −iy = x − iy = x − iy 2 2 − x + iy − x + iy 2 2 2 2 + i x − iiy +i x+y 2 2 2 2 − i x + iiy 2 2 2 −i x−y 2 = i(−i)( x − iy = i(−i x − iy = i( x + y x. Since due to properties of the norm. y = i x. and the (-1) factors may be dropped in the above expression. Reordering terms yields 4 ix. y = i(−i x − iy 2 + i x + iy 2 + x + y − x − y ). −x. The rest of the lemma follows from a similar procedure (summarised below): 4 x. y = x. y 2 − x + iy 2 +i x+y 2 − i x − y 2) + i x + iy + x+y − x − y 2) − x−y + i x + iy − i x − iy 2 ) ♦ Lemma 5.Distributing the −i results in 4 ix.

= |a|2 x and i2 = −1. y = y + x Since ax 2 2 − −y+x 2 + i iy + x 2 − i − iy + x 2 . the equation becomes x. x. the following equalities hold: − y + x = (−1)(y − x) = | − 1|2 y − x = y − x iy + x = (i)(y − ix) = |i|2 y − ix = y − ix − iy + x = (−i)(y + ix) = | − i|2 y + ix = y + ix Subsituting these expressions results in x. x. y = y + x 2 − y−x 2 + i y − ix 2 − i y + ix 2 . Swapping the positions of x and y in the norms. 2 2 2 − x − (−y) 2 + i x + i(−y) 2 − i x − i(−y) 2 + x+y 2 2 − i x − iy 2 + i x + iy 2 ) − x−y + i x + iy 2 ) − i x − iy 2 ) These of course are the desired results. Proof. Theorem 1 (Conjugate Symmetry).It is possible to rewrite this in terms of the additive inverse of y: −x. By the polarisation identity. x . y = y. y = x + y 2 − x−y 2 + i x + iy 2 − i x − iy 2 . the conjugate symmetry and positive definiteness properties are shown to hold. Another route is to factor out a (-1) on the outside of the norms: −x. y = (−1)(− x − y = (−1)( x + y = (−1) x. y . ♦ Symmetry and Definiteness In this section. −y . y = x + (−y) = x. 8 .

Due to the properties of the conjugate. Due to properties of the conjugate. Proof. x. this is the same as x. this can be written as 4 x. y = x + y = x+y 2 2 − y−x − y−x 2 2 + i y + ix + i y + ix 2 2 + −i y − ix 2 ) + −i y − ix 2 ) After subsituting y + x = x + y. By the polarisation identity. x : x. After drawing complex coefficients out of the norms and cancelling yet more. y = x + y 2 − y−x 2 − i y + ix 2 + i y − ix 2 . x = |2|2 x 2 + i|i + 1|2 x 9 2 − i|1 − i|1 x 2 . the expression inside the conjugate is y. After factoring and canceling.Using the commutative property. x . x = x + x 2 − x−x 2 + i x + ix 2 − i x − ix 2 . y = y. ♦ Theorem 2 (Transitive Inducement). the following progression is valid: i y + ix 2 + −i y − ix 2 ) = i y + ix 2 + −i y − ix 2 2 2 2 2 = i × y + ix = −i y + ix Substituting this yields x. x = 2x 2 − 0 2 + i (1 + i)x 2 − i (1 − i)x 2 . The norm used to construct the inner product can in turn be constructed from the inner product: x. y = x + y 2 2 + −i × y − ix + i × y − ix 2 = −i × y + ix + i y − ix − y−x 2 + i y + ix 2 + −i y − ix 2 ). 4 x. x = x . this becomes 4 x. .

Theorem 4 (Additive Linearity). x ≥ 0 and x. x. x. z = x + y. ♦ Linearity In this section. 0 . and so it is possible to take a square root of x. z + y. as previously shown. The positive definiteness properties of the inner product follow from the properties of the norm. x = 0 ⇐⇒ x = 0. after cancelling on both sides of the equation. z = 1 x + y. Proof. the right-hand side of the desired equation can be transformed: 1 1 x.Since |i + 1| = |1 − i|. ♦ Theorem 3 (Positive Definiteness). x = x . x ≥ 0 without a reduction in the domain. 2z . 2 10 . Using lemma 1. this reduces to 4 x. z + y. Proof. Since for a norm x ≥ 0. z = x. The details are left to the reader. x = 4 x 2 . x = x 2 . The previous equation. x 2 ≥ 0. 2 2 The term involving the zero vector equals zero and so this is x. since x. can be transformed into x. x ∈ R and x. 2z + x − y. then. Hence. the linearity properties of the inner product are shown to hold. z . x = x 2 . x + y. z + y.

y . ay = 0. this is 4 ax. ay = |a|2 x. After factoring. That is. ay = |a|2 ( x + y 2 − x−y 2 + i x + iy 2 − i x − iy 2 ). ay = |a|2 ( x + y 4 = |a|2 x. z . ay . this is the same as 4 ax. ¯ Proof. ¯ 11 . Dividing out the 4 and applying the polarisation identity again yields the desired result: 1 ax. we wish to show ax. y = x.Applying lemma 3 reduces the equation to x. y − x. By the polarisation identity. ay = ax + ay 2 − ax − ay 2 + i ax + iay 2 − i ax − iay 2 . ay = |a|2 x + y 2 − |a|2 x − y 2 + i|a|2 x + iy 2 − i|a|2 x − iy 2 . Carrying the a factor out of the norms. We establish equality by showing that the difference is zero. 4 ax. y 2 − x−y 2 + i x + iy 2 − i x − iy 2 ) ♦ Lemma 7. z + y. ay = a(x + y) 2 − a(x − y) 2 + i a(x + iy) 2 − i a(x − iy) 2 . z = x + y. ax. Proof. this becomes 4 ax. Factoring the |a|2 . ax. ♦ Lemma 6.

ay = ax. y − x. the signs can be carried in and out of the inner product: ax. (Case a ∈ R) Suppose the first case. ay + x. y − x. the signs can be carried in and out of the inner product: ax. y + ay + ax + x. ay ¯ + ax. ay = ax. y + ax. ay . ay ¯ ¯ This is essentially an equation of the form M = 2M 12 . y − ay . ¯ ¯ Using lemma 1. this is the same as ¯ ax. −ay Using lemma 5. ay = ax.We start by proving it for two cases of a: a ∈ R and a ∈ I. y + −x. y − 2 x. the inner products can be split up: ax. y − x. ay + −x. y − x. ay ¯ + ax. ay = 2 ax. y − 2 x. ay = 2 ax. y − x. ay − x. Then we use these proofs to show that it is more generally true for arbitrary a ∈ C. the sum on the right can be transformed: ax. y − x. ¯ ¯ ¯ Since a ∈ R. y + ax. y − x. −ay + x. y + x. Using lemma 5. ay Canceling terms results in ax. y − ax. y − ay . y + −x. y + ay + ax + x. ay ¯ Since a = a. the conjugate can be dropped: ax. ¯ Using the additive linearity theorem. y − x. y − x. ay = ax − x. y + ax. ay = ax − x.

−1) + i(a. The two inner products in the difference are. 1 4 and 1 4 ax + y 2 − ax − y 2 + i ax + iy 2 − i ax − iy 2 x + ay ¯ 2 − x − ay ¯ 2 + i x + i¯y a 2 − i x − i¯y a 2 . That is. we wish to show ax. −¯) + i(1. are (1) [ (a. ¯ a a a The norm terms with like coefficients. In the difference. k) = jx + ky 2 . On the other hand. we can expand the difference directly using the polarisation identity. 13 . then. ay = 0. y − x. Then the above expressions become (a. −i¯). We also drop the 4 coefficient as it does not affect whether the difference is zero. In order to make the proof a little more compact. −i) and (1. These term pairings. ¯ The use of lemma 1 would serve here as well. including sign. −¯) ] a (−1) [ (a. i) − i(a. ¯ as desired. a) − (1. ax. i) + (1. Hence. −1) + (1. may be grouped and subjected to the parallelogram law. we introduce the notation 1 (j. i¯) a ]. 1) − (a. ay = 0. y − x. respectively. i¯) − i(1. the signs for the terms of the second inner products are multiplied by −1. of course. (Case a ∈ I) As stated before.for which the only consistent solution is M = 0. we establish equality by showing that the difference is zero. −i) + (1. −i¯) ] a (−i) [ (a. 1) + (1. a) ¯ ] (i) [ (a.

Factoring out the norms. Bearing that in mind. i − i¯) + (a − 1. i) − |a − 1|2 (1. Hence a = −a. −1 − a) ] ¯ ¯ (i) [ (a + 1. −1) − |a − 1|2 (1. It should be borne in mind that |a + 1| and |a − 1| are instances of the modulus. since for a real part r and an imaginary part m. The factors of 1 arising from the parallelogram law may be dropped 2 1 for the same reason as 4 earlier. Using the parallelogram law. −1 − a) + (a − 1. i) |m|2 (j. k). i − ia) ] (−i) [ (a + 1. 1) ] (−1) [ |a + 1|2 (1. we can convert each of these pairs into a new pair. −i) + |a − 1|2 (1. −i) − |a − 1|2 (1. k) = jx + ky 2 . i) (−i) [ |a + 1|2 (1. 1) − |a − 1|2 (1. Thus Collection 1 becomes ¯ (1) [ (a + 1. −i) we have (mj. −i + i¯) + (a − 1. −1 + a) ] (i) [ (a + 1. −1) (i) [ |a + 1|2 (1. −i) [ |a + 1|2 − |a − 1|2 ] ] ] ]. 1) (−1) [ |a + 1|2 (1. 14 . |r + m| = r2 + |m|2 . −1) + |a − 1|2 (1. 1) [ |a + 1|2 − |a − 1|2 (−1) (1.It should be kept in mind that in the original difference. i) ] (−i) [ |a + 1|2 (1. as desired. 1 + a) ¯ ¯ ] (−1) [ (a + 1. the calculation of the modulus is simplified. Then the transformed terms are Collection 1 (1) [ (a + 1. We choose to group by diagonals between the first two rows. −1) [ |a + 1|2 − |a − 1|2 (i) (1. i) [ |a + 1|2 − |a − 1|2 (−i) (1. Since all of these rows are being added. 1 − a) ] (−1) [ (a + 1. −i + ia) ]. −1 + a) + (a − 1. Factoring out some ] ] ] ]. The value of the difference coefficient may be calculated using algebra. 1 − a) + (a − 1. 1 + a) + (a − 1. we can again group by like term. these rows are all being added. common factors inside the (1) [ |a + 1|2 (1. −i − i¯) ]. i + ia) + (a − 1. i + i¯) a a ] (−i) [ (a + 1. −i − ia) + (a − 1. Also. this becomes (1) (1. −i) ]. not the absolute value. a a By assumption a ∈ I. 1) + |a − 1|2 (1. the result is |a + 1|2 − |a − 1|2 = (|a|2 + 1) − (|a|2 + 1) = 0. mk) = norms yields + |a − 1|2 (1. This proves the case for a ∈ I. since a and 1 are the imaginary and real parts respectively. −1) ] (i) [ |a + 1|2 (1. Since (j. and again by diagonals for the second pair of rows: (1) [ |a + 1|2 (1.

y . y = x. Substituting this expression gives ax. ¯ The products may then be added again. y = a x. since a + ¯ = a + b. ¯ ♦ Theorem 5 (Multiplicative Linearity). y = |a|2 x. y = (m + in)x. y = x. y + inx. y . Then the other two cases can be used to carry the multiplier over: ax. It has already been proven that ax. 15 . y = mx. a Suppose a ∈ R. y = mx + inx.(Case: a ∈ C) The complex case is really a joining of the two other cases. y . ay . ax. ay = a¯x. y = x. (m + in)y . y = a2 x. y . Applying the additive linearity theorem to break up the inner product gives ax. my + in x. Proof. Then the previous equation is the same as a2 x. y = x. Let m. iny . this is equivalent to ¯ b ax. (m + in)y ¯ Of course. y . Substituting the value of a again yields the desired result: ax. reversing the earlier step: ax. n be the real and imaginary parts of a such that a = m + in.

for b = ia where a is real. y = ax. y = (a + bi)x. Since −x. since ix. Hence the lemma is true for all complex numbers. y . bx. y . y = −(−b) x. y = iax. y . It is left to the reader to consider whether the parallelogram law is a necessary as well as sufficient condition. y = ia x. y + bix. y = i ax. at least when using the polarisation identity to define the derived inner product. bx. y = − − bx. the multiplicativity is proven for b ≥ 0. y = (−b) −x.For any real number b >= 0. y = c x. y = − x. Finally for a complex number c = a + bi. ♦ 16 . y = i x. y = (a + bi) x. bx. as shown by four of the five stated theorems. y = b x. there exists an a such that b = a2 . y . y = b x. Hence the lemma holds for all b ∈ R. y . Hence. y = b x. so that for all such positive numbers b. Thus the lemma also holds for imaginary numbers. y . y + bi x. also for any b < 0. y = ax + bix. Furthermore. It may seem possible to generalize the result even more. that the regular procedure for obtaining a norm from an inner product yields the original norm that was used to construct the inner product is shown by the remaining theorem. Furthermore. cx. by finding a less restrictive condition on the norms that can be turned into inner products. y = a x. ♦ Conclusion The properties of the inner product have been satisfied under the conditions of the problem statement.